Printed coated polyester textile fabric and preparation process thereof

Through load-modified semi-carbon fibers and high-pressure jetting technology, the problem of silica powder agglomeration in the coating is solved, and the wear resistance and crack resistance of printed-coated polyester textile fabrics are improved.

CN116254709BActive Publication Date: 2025-05-02FUYANG SHUMA DECORATE ARTWARE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310230761.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-11
Publication Date
2025-05-02
Estimated Expiration
2043-03-11

AI Technical Summary

Technical Problem

In existing printed-coated polyester textile fabrics, the coating wear resistance and crack resistance are reduced because the hydroxyl group on the surface of silica powder is prone to agglomeration.

Method used

The load-modified semi-carbon fiber is adopted to improve the dispersion and three-dimensional network structure of jute fibers through semi-carbonization, activation and load treatment, and the high-pressure spraying of silica powder is combined to prevent agglomeration.

Benefits of technology

The wear resistance and crack resistance of the coating are improved, and the distribution of silica powder in the coating is more uniform, which enhances the binding force between the polyurethane resin and fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004120320760000071
    Figure BDA0004120320760000071
  • Figure BDA0004120320760000081
    Figure BDA0004120320760000081
Patent Text Reader

Abstract

The present application relates to the field of textile technology, and specifically discloses a printed coated polyester textile fabric and a preparation process thereof, wherein the printed coated polyester textile fabric includes a polyester base fabric and a polyurethane coating, and the polyurethane coating includes the following raw materials: 60-70 parts of polyurethane resin; 15-25 parts of curing agent; 5-10 parts of auxiliary agent; 8-15 parts of load-modified semi-carbonized fiber; The preparation method of load-modified semi-carbonized fiber includes the following steps: semi-carbonization treatment, placing jute fiber in a low oxygen environment below the ignition point temperature of jute fiber for semi-carbonization treatment, and obtaining semi-carbonized jute fiber; activation treatment, soaking the semi-carbonized jute fiber in a sodium hydroxide solution, after soaking, solid-liquid separation, washing, drying, and obtaining activated fiber; load treatment, fixing the activated fiber in a closed container, spraying the surface of the activated fiber with high pressure after mixing silica powder with air, shearing, and obtaining load-modified semi-carbonized fiber. The present application has the advantages of improving the wear resistance and crack resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, in particular to a printed coated polyester textile fabric and a preparation process thereof. Background Art

[0002] Coated fabric is one of the new textile varieties that has developed rapidly in recent years. It is a product obtained by coating ordinary fabrics. Coating finishing is to evenly apply one or more layers of substances such as polymers on the surface of the fabric to form a film on the surface of the fabric, which gives the fabric certain functions and even changes the appearance and style of the fabric.

[0003] The related art discloses a printed coated polyester textile fabric, in which silicon dioxide powder is added to the polyurethane coating to improve the wear resistance of the coating.

[0004] Regarding the above-mentioned related technologies, since the surface of silica powder has hydroxyl groups, it is easy to agglomerate when directly added to the coating, resulting in reduced wear resistance and crack resistance of the coating. Summary of the invention

[0005] In order to improve the wear resistance and crack resistance of the printed coating, the present application provides a printed coated polyester textile fabric and a preparation process thereof.

[0006] In the first aspect, the present application provides a printed coated polyester textile fabric, which adopts the following technical solution:

[0007] A printed coated polyester textile fabric comprises a polyester base fabric and a polyurethane coating coated on one side of the polyester base fabric, wherein the polyurethane coating comprises the following raw materials in parts by weight:

[0008] Polyurethane resin 60-70 parts;

[0009] 15-25 parts of curing agent;

[0010] 5-10 parts of additives;

[0011] 8-15 parts of modified semi-carbonized fiber are loaded;

[0012] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0013] Semi-carbonization treatment, placing the jute fiber in a low-oxygen environment at a temperature lower than the ignition point of the jute fiber for semi-carbonization treatment to obtain semi-carbonized jute fiber;

[0014] Activation treatment, soaking the semi-carbonized jute fiber in a sodium hydroxide solution, after soaking, solid-liquid separation, washing, and drying to obtain activated fiber;

[0015] In the loading treatment, the activated fiber is fixed in a sealed container, the silica powder is mixed with air and then sprayed onto the surface of the activated fiber at high pressure, and sheared to obtain the loaded modified semi-carbonized fiber.

[0016] By adopting the above technical scheme, since the surface of jute fiber contains more hydroxyl groups and is prone to agglomeration, after semi-carbonization treatment, its surface is carbonized, while the interior is not carbonized, and it still has certain strength and toughness. Therefore, the semi-carbonization treatment can improve the dispersibility of jute fiber in the coating, and the jute fiber forms a three-dimensional network structure in the coating. The surface of the carbonized layer is loose and porous, with a large specific surface area, and has a strong bonding force with the polyurethane resin, thereby improving the crack resistance of the coating; the activation treatment step removes the ash on the surface of the semi-carbonized jute fiber by immersion in alkali solution, thereby increasing the specific surface area and facilitating the pore expansion and opening of the carbonized layer; the silica powder is fixed in the micropores of the carbonized layer of the activated fiber by high-pressure spraying, thereby separating the silica powder and reducing the possibility of agglomeration of the silica powder, thereby making the silica powder more evenly distributed in the coating, improving the wear resistance of the coating, and further improving the crack resistance of the coating.

[0017] Optionally, in the semi-carbonization treatment step, the temperature is controlled to be 280-290° C., the insulation time is 10-15 min, and the oxygen volume fraction in the low-oxygen environment is 0.8-1.2%.

[0018] By adopting the technical solution, the jute fiber is semi-carbonized at a temperature below the ignition point, thereby reducing the probability of complete carbonization.

[0019] Optionally, in the activation treatment step, the mass concentration of the sodium hydroxide solution is 20-30%wt, and the soaking time is 30-60min.

[0020] By adopting the above technical solution, the sodium hydroxide solution can increase the specific surface area and pore volume of the carbonized layer of the jute fiber, which is beneficial for the silicon dioxide powder to enter the micropores of the carbonized layer.

[0021] Optionally, in the loading treatment step, the mass ratio of silica powder to activated fiber is (4-6):10.

[0022] By adopting the above technical solution, if there is too much silica powder, it is easy to block all the micropores of the carbonized layer, which will reduce the bonding force between the loaded modified semi-carbonized fiber and the polyurethane resin; if there is too little silica powder, the wear resistance of the coating will be improved to a small extent.

[0023] Optionally, in the loading treatment step, the silicon dioxide powder is mixed with air and then sprayed onto the surface of the activated fiber at a pressure of 3-5 MPa, and the spraying time is 35-40 minutes.

[0024] By adopting the above technical solution, the silicon dioxide powder is firmly fixed in the micropores on the surface of the carbonized layer through high-pressure spraying.

[0025] Optionally, in the loading treatment step, the length of the loaded modified semi-carbonized fibers is 2-4 mm.

[0026] By adopting the above technical solution, the length of the loaded modified semi-carbonized fiber is too short, which is not conducive to improving the crack resistance of the coating; the length of the loaded modified semi-carbonized fiber is too long, which is not conducive to preparing a thinner coating.

[0027] Optionally, in the loading treatment step, a coating treatment is further performed after shearing: an organic resin emulsion is sprayed onto the surface of the activated fiber after shearing, and solidified to obtain loaded modified semi-carbonized fiber.

[0028] By adopting the above technical solution, the organic resin emulsion is wrapped on the surface of the activated fiber, which reduces the probability of silicon dioxide powder falling off and is conducive to uniform dispersion of the loaded modified semi-carbonized fiber in the polyurethane resin.

[0029] Optionally, the mass ratio of the activated fiber to the organic resin emulsion is 100:(20-30).

[0030] By adopting the above technical solution, if the amount of organic resin emulsion is too large, the wrapping layer is too thick, which is not conducive to improving wear resistance; if the amount of organic resin emulsion is too small, the wrapping layer is too thin, the silica powder may fall off, and it is not conducive to uniform dispersion of the loaded modified semi-carbonized fiber in the polyurethane resin.

[0031] In a second aspect, the present application provides a method for preparing a printed coated polyester textile fabric, using the following technical solution:

[0032] A preparation process of a printed coated polyester textile fabric comprises the following steps:

[0033] Step 1, uniformly mixing polyurethane resin, curing agent, auxiliary agent and loaded modified semi-carbonized fiber to obtain a coating;

[0034] Step 2: evenly apply the coating on one side of the polyester base fabric and solidify it to obtain a printed coated polyester textile fabric.

[0035] By adopting the above technical scheme, the silica powder is fixed in the micropores of the carbonized layer of the activated fiber through high-pressure spraying, thereby separating the silica powder and reducing the possibility of silica powder agglomeration, so that the silica powder is more evenly distributed in the coating, thereby improving the wear resistance of the coating; the loaded modified semi-carbonized fiber forms a three-dimensional network structure in the coating, the surface of the carbonized layer is loose and porous, the specific surface area is large, and the bonding force with the polyurethane resin is strong, thereby improving the crack resistance of the coating.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Since the silica powder of the present application is fixed in the micropores of the carbonized layer of the activated fiber through high-pressure spraying, the silica powder is separated, reducing the possibility of silica powder agglomeration, so that the silica powder is more evenly distributed in the coating, thereby improving the wear resistance of the coating; the loaded modified semi-carbonized fiber forms a three-dimensional network structure in the coating, the surface of the carbonized layer is loose and porous, the specific surface area is large, and the bonding force with the polyurethane resin is strong, thereby improving the crack resistance of the coating.

[0038] 2. In the present application, it is preferred to coat the activated fiber, and the organic resin emulsion is wrapped on the surface of the activated fiber, which reduces the probability of silica powder falling off and is conducive to uniform dispersion of the loaded modified semi-carbonized fiber in the polyurethane resin. DETAILED DESCRIPTION

[0039] The present application is further described in detail below in conjunction with embodiments.

[0040] Preparation example of loaded modified semi-carbonized fiber

[0041] Preparation Example 1

[0042] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0043] Semi-carbonization treatment, placing the dried jute fiber in an environment with a temperature of 280° C. and an oxygen volume fraction of 0.8% for semi-carbonization treatment for 15 minutes to obtain semi-carbonized jute fiber;

[0044] Activation treatment: soaking the semi-carbonized jute fiber in a sodium hydroxide solution with a mass concentration of 20%wt for 60 minutes, filtering, washing, and drying to obtain activated fiber;

[0045] For load treatment, the activated fiber was suspended and fixed in a closed container, and the silica powder was mixed with air and sprayed onto the surface of the activated fiber at a pressure of 2 MPa. The spraying time was 35 min, and the mass ratio of silica powder to activated fiber was 2:10. After shearing, load-modified semi-carbonized fibers with a length of 2 mm were obtained.

[0046] Preparation Example 2

[0047] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0048] Semi-carbonization treatment, placing the dried jute fiber in an environment with a temperature of 285° C. and an oxygen volume fraction of 1% for semi-carbonization treatment for 12 minutes to obtain semi-carbonized jute fiber;

[0049] Activation treatment, soaking the semi-carbonized jute fiber in a sodium hydroxide solution with a mass concentration of 25%wt for 45 minutes, filtering, washing with water, and drying to obtain activated fiber;

[0050] For load treatment, the activated fiber was suspended and fixed in a closed container, and the silica powder was mixed with air and sprayed onto the surface of the activated fiber at a pressure of 2 MPa. The spraying time was 38 min, and the mass ratio of silica powder to activated fiber was 2:10. After shearing, load-modified semi-carbonized fibers with a length of 3 mm were obtained.

[0051] Preparation Example 3

[0052] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0053] Semi-carbonization treatment, placing the dried jute fiber in an environment with a temperature of 290° C. and an oxygen volume fraction of 1.2% for semi-carbonization treatment for 10 minutes to obtain semi-carbonized jute fiber;

[0054] Activation treatment, soaking the semi-carbonized jute fiber in a sodium hydroxide solution with a mass concentration of 30%wt for 30 minutes, filtering, washing with water, and drying to obtain activated fiber;

[0055] For load treatment, the activated fiber was suspended and fixed in a closed container, and the silica powder was mixed with air and sprayed onto the surface of the activated fiber at a pressure of 2 MPa. The spraying time was 40 min, and the mass ratio of silica powder to activated fiber was 2:10. After shearing, load-modified semi-carbonized fibers with a length of 4 mm were obtained.

[0056] Preparation Example 4

[0057] The difference from Preparation Example 2 is that the mass ratio of silica powder to activated fiber is 4:10.

[0058] Preparation Example 5

[0059] The difference from Preparation Example 2 is that the mass ratio of silica powder to activated fiber is 5:10.

[0060] Preparation Example 6

[0061] The difference from Preparation Example 2 is that the mass ratio of silica powder to activated fiber is 6:10.

[0062] Preparation Example 7

[0063] The difference from Preparation Example 2 is that the mass ratio of silica powder to activated fiber is 8:10.

[0064] Preparation Example 8

[0065] The difference from Preparation Example 5 is that the spray pressure in the supporting treatment step was 3 MPa.

[0066] Preparation Example 9

[0067] The difference from Preparation Example 5 is that the spray pressure in the supporting treatment step was 4 MPa.

[0068] Preparation Example 10

[0069] The difference from Preparation Example 5 is that the spray pressure in the supporting treatment step was 5 MPa.

[0070] Preparation Example 11

[0071] The difference from Preparation Example 5 is that the spray pressure in the supporting treatment step was 7 MPa.

[0072] Preparation Example 12

[0073] The difference from Preparation Example 9 is that in the loading treatment step, a coating treatment is also carried out after shearing: a spray drying process is used to apply a polyurethane resin emulsion to the surface of the activated fiber after shearing. The polyurethane resin emulsion is PU-268 purchased from Dongguan Xincai Environmental Protection Technology Co., Ltd. The mass ratio of the activated fiber after shearing to the polyurethane resin emulsion is 100:20, and it is cured at 100°C to obtain a loaded modified semi-carbonized fiber.

[0074] Preparation Example 13

[0075] The difference from Preparation Example 12 is that the mass ratio of the activated fibers after shearing to the polyurethane resin emulsion is 100:25.

[0076] Preparation Example 14

[0077] The difference from Preparation Example 12 is that the mass ratio of the activated fibers after shearing to the polyurethane resin emulsion is 100:30.

[0078] Comparative Preparation Example 1

[0079] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0080] Semi-carbonization treatment, placing the dried jute fiber in an environment with a temperature of 285° C. and an oxygen volume fraction of 1% for semi-carbonization treatment for 12 minutes to obtain semi-carbonized jute fiber;

[0081] For load treatment, the semi-carbonized jute fiber was suspended and fixed in a closed container, and the silica powder was mixed with air and sprayed onto the surface of the semi-carbonized jute fiber at a pressure of 2 MPa. The spraying time was 38 min, and the mass ratio of silica powder to semi-carbonized jute fiber was 2:10. After shearing, load-modified semi-carbonized fiber with a length of 3 mm was obtained.

[0082] Comparative Preparation Example 2

[0083] The preparation method of the loaded modified semi-carbonized fiber comprises the following steps:

[0084] Activation treatment, soaking the dried jute fiber in a sodium hydroxide solution with a mass concentration of 25%wt for 45 minutes, filtering, washing with water, and drying to obtain activated fiber;

[0085] For load treatment, the activated fiber was suspended and fixed in a closed container, and the silica powder was mixed with air and sprayed onto the surface of the activated fiber at a pressure of 2 MPa. The spraying time was 38 min, and the mass ratio of silica powder to activated fiber was 2:10. After shearing, load-modified semi-carbonized fibers with a length of 3 mm were obtained.

[0086] Example

[0087] Example 1

[0088] A printed coated polyester textile fabric comprises a polyester base fabric and a polyurethane coating coated on one side of the polyester base fabric, wherein the polyurethane coating comprises the following raw materials by weight:

[0089] 60 kg of polyurethane resin, the polyurethane resin is PU-268 purchased from Dongguan Xincai Environmental Protection Technology Co., Ltd.;

[0090] 15kg of curing agent, the curing agent is BayhydrolXP2547;

[0091] 5kg of auxiliary agent, the auxiliary agent is dipropylene glycol methyl ether;

[0092] 8 kg of the loaded modified semi-carbonized fiber was prepared by Preparation Example 1.

[0093] The preparation process of the printed coated polyester textile fabric comprises the following steps:

[0094] Step 1: mix the polyurethane resin, curing agent, auxiliary agent and loaded modified semi-carbonized fiber, stir evenly to obtain a coating; Step 2: evenly apply the coating on one side of the polyester base fabric, bake and cure at 100°C to obtain a printed coated polyester textile fabric.

[0095] Embodiment 2-14

[0096] The difference from Example 1 is that the loaded modified semi-carbonized fiber is prepared in sequence from Preparation Examples 2-14.

[0097] Embodiment 15

[0098] The difference from Example 13 is that the polyurethane coating includes the following raw materials by weight:

[0099] Polyurethane resin 65kg;

[0100] Curing agent 20kg;

[0101] Additives 8kg;

[0102] The modified semi-carbonized fiber was loaded with 12 kg.

[0103] Example 16

[0104] The difference from Example 13 is that the polyurethane coating includes the following raw materials by weight:

[0105] Polyurethane resin 70kg;

[0106] Curing agent 25kg;

[0107] Additives 10kg;

[0108] The modified semi-carbonized fiber was loaded with 15 kg.

[0109] Comparative Example

[0110] Comparative Example 1-2

[0111] The difference from Example 2 is that the loaded modified semi-carbonized fiber is prepared by Comparative Preparation Examples 1-2 in sequence.

[0112] Comparative Example 3

[0113] The difference from Example 2 is that the polyurethane coating includes the following raw materials by weight:

[0114] Polyurethane resin 60kg;

[0115] Curing agent 15kg;

[0116] Additives 5kg;

[0117] 1.33 kg of silicon dioxide powder;

[0118] Jute fiber 6.67kg, length 3mm;

[0119] The preparation process of the printed coated polyester textile fabric comprises the following steps:

[0120] Step 1, mixing polyurethane resin, curing agent, additive, silica powder and jute fiber, stirring evenly to obtain a coating;

[0121] Step 2: evenly apply the coating on one side of the polyester base fabric, bake and cure at 100° C. to obtain a printed coated polyester textile fabric.

[0122] Comparative Example 4

[0123] The difference from Example 2 is that the polyurethane coating includes the following raw materials by weight:

[0124] Polyurethane resin 60kg;

[0125] Curing agent 15kg;

[0126] Additives 5kg;

[0127] 1.33 kg of silicon dioxide powder;

[0128] The preparation process of the printed coated polyester textile fabric comprises the following steps:

[0129] Step 1, mixing polyurethane resin, curing agent, auxiliary agent and silicon dioxide powder, stirring evenly to obtain a coating;

[0130] Step 2: evenly apply the coating on one side of the polyester base fabric, bake and cure at 100° C. to obtain a printed coated polyester textile fabric.

[0131] Performance testing

[0132] Detection Methods

[0133] (1) Mechanical property test: The tensile strength at break of Examples 1-16 and Comparative Examples 1-4 was tested on a universal tensile testing machine according to standard ASTM D638, with a tensile test rate of 45 mm / min.

[0134] (2) Wear resistance test: The Martinelle method and its standard system were used to test the number of breakage frictions and the wear mass loss of Examples 1-16 and Comparative Examples 1-4.

[0135] Table 1 Test results

[0136]

[0137] Combining Examples 1-16 and Comparative Examples 1-4 and Table 1, it can be seen that Comparative Example 4 only adds silica powder, and the tensile fracture strength and the number of damage frictions are the smallest, and the wear mass loss is the largest, indicating that the silica powder is easily agglomerated when directly added to the coating, and the wear resistance and crack resistance of the coating are poor. Comparative Example 3 adds jute fiber on the basis of Comparative Example 4, and the tensile fracture strength and the number of damage frictions are improved, and the wear mass loss is reduced, indicating that jute fiber can improve the wear resistance and crack resistance of the coating; Comparative Example 2 does not have a semi-carbonization treatment step, and the tensile fracture strength and the number of damage frictions are The number is higher than that of comparative example 3 and lower than that of example 2, the wear quality loss is lower than that of comparative example 3, but higher than that of example 2. Comparative example 1 does not have an activation treatment step, and the tensile fracture strength and the number of damage friction times are higher than those of comparative example 3 and lower than those of example 2, and the wear quality loss is lower than that of comparative example 3, but higher than that of example 2. Examples 1-3 are prepared by semi-carbonization treatment, activation treatment and loading treatment to obtain loaded modified semi-carbonized fibers, and the tensile fracture strength and the number of damage friction times are greatly improved, and the wear quality loss is greatly reduced. Among them, the comprehensive effect of example 2 is better, indicating that the loaded modified semi-carbonized fibers can improve the wear resistance of the coating. and crack resistance; Examples 4-7 gradually increase the amount of silica powder, the tensile strength and the number of breakage frictions first increase and then decrease, and the wear mass loss gradually decreases, but the reduction in Preparation Example 7 is very small, and the effect of Example 5 is better, indicating that the mass ratio of silica powder to activated fiber is preferably (4-6):10; Examples 8-11 gradually increase the injection pressure, the tensile strength and the number of breakage frictions first increase and then decrease, and the wear mass loss first decreases and then increases, and the effect of Example 9 is better, indicating that the injection pressure is preferably 3-5MPa; Preparation Examples 12-14 at the activated The fiber surface is coated with organic resin, the tensile breaking strength and the number of breakage friction times are increased, and the wear mass loss is reduced. The effect of Example 13 is better, which may be because the organic resin is wrapped on the surface of the activated fiber, reducing the probability of silica powder falling off, and is beneficial to the uniform dispersion of the loaded modified semi-carbonized fiber in the polyurethane resin, thereby improving the wear resistance and crack resistance of the coating; Examples 15-16 changed the raw material ratio of the polyurethane coating, and the tensile breaking strength, breakage friction times and wear mass loss all changed, indicating that the ratio of raw materials will affect the wear resistance and crack resistance of the polyurethane coating.

[0138] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A printed coated polyester textile fabric, characterized in that: It comprises a polyester base fabric and a polyurethane coating coated on one side of the polyester base fabric, wherein the polyurethane coating comprises the following raw materials in parts by weight: Polyurethane resin 60-70 parts; 15-25 parts of curing agent; 5-10 parts of additives; 8-15 parts of modified semi-carbonized fiber are loaded; The preparation method of the loaded modified semi-carbonized fiber comprises the following steps: Semi-carbonization treatment, placing the jute fiber in a low-oxygen environment at a temperature lower than the ignition point of the jute fiber for semi-carbonization treatment to obtain semi-carbonized jute fiber; Activation treatment, soaking the semi-carbonized jute fiber in a sodium hydroxide solution, after soaking, solid-liquid separation, washing, and drying to obtain activated fiber; In the loading treatment, the activated fiber is fixed in a sealed container, the silica powder is mixed with air and then sprayed onto the surface of the activated fiber at high pressure, and sheared to obtain the loaded modified semi-carbonized fiber.

2. The printed coated polyester textile fabric according to claim 1, characterized in that: In the semi-carbonization treatment step, the temperature is controlled at 280-290° C., the insulation time is 10-15 minutes, and the oxygen volume fraction in the low-oxygen environment is 0.8-1.2%.

3. The printed coated polyester textile fabric according to claim 1, characterized in that: In the activation treatment step, the mass concentration of the sodium hydroxide solution is 20-30%wt, and the soaking time is 30-60min.

4. The printed coated polyester textile fabric according to claim 1, characterized in that: In the loading treatment step, the mass ratio of silica powder to activated fiber is (4-6):

10.

5. The printed coated polyester textile fabric according to claim 4, characterized in that: In the loading treatment step, the silicon dioxide powder is mixed with air and then sprayed onto the surface of the activated fiber at a pressure of 3-5 MPa for 35-40 minutes.

6. The printed coated polyester textile fabric according to claim 5, characterized in that: In the loading treatment step, the length of the loaded modified semi-carbonized fibers is 2-4 mm.

7. A printed coated polyester textile fabric according to any one of claims 1 to 6, characterized in that: In the loading treatment step, a coating treatment is also performed after shearing: an organic resin emulsion is sprayed onto the surface of the activated fiber after shearing, and solidified to obtain loaded modified semi-carbonized fiber.

8. The printed coated polyester textile fabric according to claim 7, characterized in that: The mass ratio of the activated fiber to the organic resin emulsion is 100:(20-30).

9. The process for preparing the printed coated polyester textile fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, uniformly mixing polyurethane resin, curing agent, auxiliary agent and loaded modified semi-carbonized fiber to obtain a coating; Step 2: evenly apply the coating on one side of the polyester base fabric and solidify it to obtain a printed coated polyester textile fabric.

Citation Information

Patent Citations

  • Inkjet printing coating of textile

    CN105734955A

  • Lightweight concrete and preparation method thereof

    CN114716188A